Perbandingan Awal Waktu Salat Berdasarkan Sudut Depresi Matahari 18°, 19°, Dan 20° Menurut Kajian Hadis Falak - Fani Faizatur Rahmah; Muhammad Farihul Umam Al Firdausi; Wildana Albi Chabibah (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Astronomical studies on the determination of prayer times, particularly for the Fajr and Isha prayers, often employ different solar depression angles as the basis of calculation. This study compares the determination of the beginning of prayer times using solar depression angles of 18°, 19°, and 20° to examine how variations in these angles affect the resulting time differences. Using an astronomical analysis approach, the differences in angles were found to produce a significant time discrepancy, especially for the Fajr prayer, which is more sensitive to changes in solar depression. The results of this comparison provide valuable insights for institutions responsible for establishing official prayer timetables and for the wider Muslim community. These findings can serve as a reference in developing more accurate and astronomically consistent criteria for determining prayer times.